Good outcome case of anterior cerebral artery dissection that was treated with recombinant tissue plasminogen activator and trapping with A3‐A3 anastomosis surgery. Issue 5 (26th July 2016) - Sugimura, Yusuke; Koike, Kazunari; Terao, Satoshi; Asada, Hideo
Abstract: A 41‐year‐old Japanese man was diagnosed with acute ischemic stroke in the emergency room. He was given recombinant tissue plasminogen activator within a suitable time frame and symptoms were improved. However, follow‐up magnetic resonance imaging showed asymptomatic expansion of the ischemic infarction, and 3‐D computed tomography angiography showed the pearl and string sign of the left anterior cerebral artery. Then, trapping with A3‐A3 anastomosis surgery was successfully carried out. This is a very rare case of a patient who was treated with recombinant tissue plasminogen activator and had a good outcome, and also had trapping with A3‐A3 anastomosis surgery for an anterior cerebral artery dissecting aneurysm. However, because the pathology was determined to be dissection to the outer membrane, there was a risk of subarachnoid hemorrhage during the recombinant tissue plasminogen activator treatment. Cerebral arterial dissection is a disease that should not be forgotten, and that treatment is very difficult.